“The Simple Question of Ireland”: La Reine de beauté de Leenane in Montreal - Fricker, Karen (Theatre Research in Canada / Recherches théâtrales au Canada, 2014)
This article uses the tools of intercultural and translation theory to explore the production and reception of La Reine de beauté de Leenane, the 2001 French language premiere of Martin McDonagh’s The Beauty Queen of Leenane, translated by Fanny Britt and produced by Théâtre La Licorne in Montreal. Creative team and critics alike understood the play as a realistic tragicomedy, and valued the production for the parallels it offered to real-life conditions of rural underdevelopment in contemporary Quebec, and for the ways in which the play’s depiction of Ireland was understood to resonate with Quebec’s own problematic postcoloniality. Such a reading does not take on board the strong current of exaggeration in McDonagh’s text nor the extent to which the play offers a satiric commentary on Irishness (and national identity more broadly) as commodity. The article weighs the positive effects of the sense of self-recognition and solidarity Quebecois artists and critics located in the play against the fact that inaccurate and misleading information about Ireland was disseminated via the production and its critical reception. Understanding this and other productions of plays in translation as intercultural encounters, the article advocates for the presence of interlocuters in such exchanges, who can speak on behalf the culture being represented.